Childhood obesity: the epidemic of the third millenium - Archenti, A.; Pasqualinotto, L. (Acta Biomedica Atenei Parmensis, 2008)
Background: Italy is the European country with the most obese and overweight children and teenagers. Most of them have a family history of obesity and this condition may increase the risk of many diseases. Methods: This study involved 52 patients (32 females and 20 males) between 6 and 17 years of age with an average BMI of 31.5.The patients underwent a three-month treatment which included an overview of individual caloric intake and creation of a suitable diet, an exercise program and counselling sessions with a psychologist in order to support the patients and families. Anthropometric changes were evaluated at the end of the three months and during follow-up to assess the effectiveness of the treatment. Results: Before starting the treatment the average weight of the patients was 81.8 kg, after the treatment it decreased to 79.4 kg. Likewise, the average BMI of the patients was 31.3 before the treatment and 30.4 after the treatment. Both of these results are statistically significant. Conclusions: This study confirms the importance of teamwork in the treatment of childhood obesity and the importance of approaching the problem with the entire family. A real problem exists for patients who are strongly dependent on the habits, determination and flexibility of their family. In conclusion, the success of this treatment is strongly related to the psychological attitude of the family.